Kazan University in the early 1870s as seen by a Kievan Master of Science: Some comments on the Master's thesis defense by I.V. Luchitsky - S.I. Luchitskaya (Ученые записки Казанского университета: Серия Гуманитарные науки)
The year 2021 marks 150 years since the great Russian and Ukrainian historian, the representative of the école russe Ivan Vasilievich Luchitsky defended his Master’s thesis at the Kazan University. This article publishes for the first time seven letters by I.V. Luchitsky preserved in his personal collection at the Institute of Manuscript of Vernadsky National Library of Ukraine. The letters presented here were written in Kazan where the young scholar arrived early in October 1871 in order to defend his thesis titled “Feudal Aristocracy and Calvinists in France” before the jury of the Imperial Kazan University. The publication of the handwritten sources is essential for several reasons: firstly, they bring to light some new facts about the historian’s biography; secondly, they give an idea of the thesis defense procedure in the post-reform Russia; thirdly, they describe the daily life of the Kazan University in the early 1870s, thus being a valuable source for historians. Besides the letters, the scholars and public figures of Kazan who were famous during that period are characterized.